2015
DOI: 10.1371/journal.pone.0131793
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5-Aminolevulinic Acid on Cytochrome P450-Mediated Prodrug Activation

Abstract: Of late, numerous prodrugs are widely used for therapy. The hemeprotein cytochrome P450 (CYP) catalyzes the activation of prodrugs to form active metabolites. Therefore, the activation of CYP function might allow the use of lower doses of prodrugs and decrease toxicity. We hypothesized that the addition of 5-aminolevulinic acid (ALA), a precursor in the porphyrin biosynthetic pathway, enhances the synthesis of heme, leading to the up-regulation of CYP activity. To test this hypothesis, we treated a human gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Protoporphyrin IX is used in cancer treatment to identify and destroy tumors by photodynamic diagnosis and therapy . The insertion of ferrous ion into PpIX generates haem in the mitochondria . Additionally, 5‐ALA is known to induce haem oxygenase‐1 (HO‐1) in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Protoporphyrin IX is used in cancer treatment to identify and destroy tumors by photodynamic diagnosis and therapy . The insertion of ferrous ion into PpIX generates haem in the mitochondria . Additionally, 5‐ALA is known to induce haem oxygenase‐1 (HO‐1) in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Minura et al . furthermore showed that the addition of 5 aminolevulinic acid (5‐ALA), a precursor of the porphyrin biosynthesis, led to the up‐regulation of the P450 CYP2A6 activity and prodrug activation . Addition of 5‐ALA in the exponential phase, however, did not show further improvement of the conversion (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of vertebrates and vertebrate cell lines support the hypothesis that exogenous 5‐ALA enhances haem synthesis and activity of haemoproteins: 5‐ALA administration (a) increased intracellular haem levels, increasing the activity of cytochrome P450 in vitro (Miura et al., ); (b) increased the activity of cytochrome c oxidase of the electron transport chain and raised ATP levels in mouse liver (Ogura et al., ); (c) enhanced protein expression of mitochondrial complexes III–V in mouse adipose tissue (Ota et al., ); (d) induced REV‐ERBα expression (Yamashita et al., ); and (e) induced both protein and mRNA expression of haem oxygenase‐1 (HO‐1) (a rate‐limiting enzyme in haem degradation) (Nishio et al., : Ito et al., ). 5‐aminolevulinic acid was also reported to enhance the immune response in chickens (Sato et al., ) and pigs (Chen et al., ) and improves growth performance in eels (Yasumoto, Miyanari, Yoshimura, Kondo & Takahashi, ) (although there is some disagreement on the effect of 5‐ALA on growth; see below).…”
Section: Introductionmentioning
confidence: 94%
“…Several studies of vertebrates and vertebrate cell lines support the hypothesis that exogenous 5-ALA enhances haem synthesis and activity of haemoproteins: 5-ALA administration (a) increased intracellular haem levels, increasing the activity of cytochrome P450 in vitro (Miura et al, 2015); (b) increased the activity of cytochrome c oxidase of the electron transport chain and raised ATP levels in mouse liver (Ogura et al, 2011); (c) enhanced protein expression of mitochondrial complexes III-V in mouse adipose tissue (Ota et al, 2017); (d) induced REV-ERBα expression (Yamashita et al, 2014);…”
mentioning
confidence: 92%
See 1 more Smart Citation